1995
DOI: 10.1007/bf02033667
|View full text |Cite
|
Sign up to set email alerts
|

Antennal perception of oilseed rape,Brassica napus (Brassicaceae), volatiles by the cabbage seed weevilCeutorhynchus assimilis (Coleoptera, Curculionidae)

Abstract: The response of theCeutorhynchus assimilis antenna to volatiles in air entrainment-derived extracts of oilseed rape,Brassica napus, was studied using coupled gas chromatography (GC)-electroantennography (EAG) and coupled GC-single cell recording (SCR). By means of these techniques and coupled gas chromatography-mass spectrometry (GC-MS), 25 active compounds were identified, including isoprenoids and compounds derived from fatty acids and amino acids. Some of the latter, the isothiocyanates and goitrin, and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 18 publications
3
81
0
Order By: Relevance
“…Functional characterization of this ORN in conjunction with behavioral testing of the ligand would be desirable in order to consolidate the relevance of ORN interactions. In fact, inhibition of Acells when Bcells respond seems to be a common phenomenon (Blight et al, 1995;Hallem et al, 2004;), but it has not been systematically addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Functional characterization of this ORN in conjunction with behavioral testing of the ligand would be desirable in order to consolidate the relevance of ORN interactions. In fact, inhibition of Acells when Bcells respond seems to be a common phenomenon (Blight et al, 1995;Hallem et al, 2004;), but it has not been systematically addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Green leaf volatiles and specific host-related compounds were demonstrated to play a significant role in overall perception and recognition of host odour. In a response study with cabbage seed weevil antenna to volatiles in air entrainment-derived extracts of oilseed rape, using electroantennograms coupled with GC-single cell recording, it was shown that isothiocyanate perception is mediated by three types of olfactory cells, which show differential response to 3-butenyl, 4-pentenyl and 2-phenylethyl isothiocyanate (Blight et al, 1995). The responses of cabbage seed weevil to other electrophysiologically-active volatiles from rape were tested in a linear track olfactometer (Bartlet et al, 1997).…”
Section: Plants (Brassica Spp)-herbivores (Ceutorhynchus Assimilis)mentioning
confidence: 99%
“…Some insects can identify unsuitable hosts by detecting ratios of common plant components * Corresponding author: sunjh@ioz.ac.cn not normally encountered in suitable hosts [5,25,26]. The importance of terpenes present in coniferous trees as oviposition stimulants or feeding deterrents to bark and wood boring insects has been well established [1,12,14,21].…”
Section: Introductionmentioning
confidence: 99%